Inappropriate Use of Parenteral Analgesics for Mild Pain and Uncomplicated Fever in the Emergency Department: Findings from an Internal Audit - Dewi, Rissa Maharani; Rosyid, Abdur; Timur, Willi Wahyu; Nastiti, Nindita Sari; Ningrum, Dwi Monika; Widiyanto, Dimas (Sciences of Pharmacy, 2026)
Inappropriate prescribing of parenteral analgesics in patients with mild pain or uncomplicated fever remains a relevant concern in emergency care. This study reports findings from a retrospective internal audit conducted in the emergency department of a private hospital in Banjarbaru, Indonesia, to evaluate the appropriateness of non-steroidal anti-inflammatory drug (NSAID) use. Medical records of 384 emergency department visits were reviewed, including data on pain intensity using the Numeric Rating Scale (NRS), clinical indications, route of administration, and immediate adverse reactions. Inappropriate use was defined as administration of parenteral NSAIDs in patients with mild pain (NRS 1–3) or uncomplicated fever when oral therapy was feasible, based on Royal College of Emergency Medicine (RCEM) guidelines. The audit identified inappropriate parenteral NSAID use in 7 patients (3.6%). These cases were associated with mild, immediate adverse effects such as nausea and dizziness. Although the proportion was small, the findings indicate potentially avoidable use of injectable analgesics and highlight the need for improved adherence to guideline-based analgesic selection. Reinforcement of routine pain assessment, clinician re-education, and periodic prescribing audits are recommended to support rational and patient-centered analgesic use in emergency settings.